An Improved Synthesis of Balsaminone A - Daley, Sharna-kay A.; Downer-Riley, Nadale K. (Synlett, 2019)
A short and efficient synthesis of balsaminone A, a dinaphthofuran-1,4-dione, is described. The eight-step synthesis features two alternate pathways including a base-induced coupling reaction of 4-methoxy-1-naphthol and 2,3-dichloro-1,4-naphthoquinone, as well as a light-mediated cyclization of 1,1'-binaphthoquinone to afford the dinaphthofurandione core. Subsequent ortho formylation yielded a known precursor to balsaminone A, affording the natural product in 20–27% yield. This represents a moderate increase from the previous synthesis of 7.4% yield.
Keywords: balsaminone A; Liebermann coupling; light-mediated cyclization; naphthofurandione; natural products